Can the Development of AKI be Predicted in COVID-19 Patients with Severe Pneumonia? - Rabia Sarı Küçük; Asime Ay; Esra Dağlı; Rabia Gülsüm Aydın; Namigar Turgut (Galenos Yayinevi, 2022)
Objective: Coronavirus disease-2019 (COVID-19) may cause severe respiratory disease, glomerular dysfunction and acute tubular necrosis. Lactate dehydrogenase (LDH), C-reactive protein (CRP), D-dimer, lymphopenia and increased neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR) associated with poor prognosis. We investigated the effects of these mediators on the development of acute kidney injury (AKI). Materials and Methods: Patients with severe pneumonia with the diagnosis COVID-19 were included in the retrospective study. Three subgroups were created: Group 1: patients who developed AKI at admission or at follow-up to the intensive care unit (ICU), group 2: those without AKI, group 3: Patients who developed AKI on the basis of chronic kidney disease. Demographic data, comorbidities, lactate, D-dimer, CRP, LDH, NLR, PLR, mortality were recorded and compared. Results: Two hundred fifty six patients were evaluated. Group 2 D-dimer levels before ICU were significantly lower than those in group 3. Group 2 last day D-dimer levels were significantly lower than those of group 3 and group 1. Admission LDH values were higher in the group 1 than in groups 2 and 3. Last day LDH values were higher in the group 1 than in group 2. NLR values were higher in group 3 than in group 2 on the 6th day. Last day PLR values were lower in the group 1 than in group 2. No significant difference was present between the groups in terms of D-dimer, LDH, NLR, PLR levels at the other time points. Conclusion: The contribution of laboratory findings in determining the risk of AKI has not been clarified.